2018
DOI: 10.1016/j.tranon.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

CBX1 Indicates Poor Outcomes and Exerts Oncogenic Activity in Hepatocellular Carcinoma

Abstract: Dysregulation of chromobox proteins contributes to the progression of human diseases. CBX1 has been implicated in epigenetic control of chromatin structure and gene expression, but its role in human cancers remains largely unknown. Here we show that CBX1 exhibits oncogenic activities in hepatocellular carcinoma (HCC) and indicates poor outcomes. The expression of CBX1 was noticeably increased, at both mRNA and protein levels, in HCC tissues and cell lines, compared with the nontumorous ones. High CBX1 expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 31 publications
1
52
0
Order By: Relevance
“…Yang et al [12] also discovered that CBX1 protein expression was dramatically upregulated in HCC. It was suggested that HCC patients with elevated levels of CBX1 had shorter survival times and tumor recurrence times [12]. Recently, Liang et al [27] revealed that high expression of CBX1 might be predictive for poor clinical outcomes in breast cancer, especially in estrogen receptor-positive patients.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Yang et al [12] also discovered that CBX1 protein expression was dramatically upregulated in HCC. It was suggested that HCC patients with elevated levels of CBX1 had shorter survival times and tumor recurrence times [12]. Recently, Liang et al [27] revealed that high expression of CBX1 might be predictive for poor clinical outcomes in breast cancer, especially in estrogen receptor-positive patients.…”
Section: Discussionmentioning
confidence: 98%
“…One study indicated that CBX1 was a key regulator in regulating cell differentiation and proliferation, and silencing CBX1 inhibited prostate cancer cell proliferation [26]. Yang et al [12] also discovered that CBX1 protein expression was dramatically upregulated in HCC. It was suggested that HCC patients with elevated levels of CBX1 had shorter survival times and tumor recurrence times [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Elevated expression of VCAN predicted worse outcomes for patients as shorter survival times were observed in the high expression group compared with the low expression group. Again, previous evidence had documented the associations between upregulated gene expressions and poor patients outcome (41)(42)(43)(44) and VCAN had been reported as an unfavorable prognostic marker in oral squamous cell carcinoma and endometrial cancer (11,45). VCAN expression in gastric cancer may be a potential diagnostic tool and a marker of poor outcome for patients.…”
Section: Discussionmentioning
confidence: 90%